2019
DOI: 10.5114/wiitm.2019.84384
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Fowler positioning in addition to the pulmonary recruitment manoeuvre reduces shoulder pain following gynaecologic laparoscopic surgery.

Abstract: IntroductionThe semi-Fowler position, defined as a body position at 30° head-of-bed elevation, has been shown to increase intra-abdominal pressure.AimTo investigate the impact of semi-Fowler positioning in addition to the pulmonary recruitment manoeuvre (PRM) on post-laparoscopic shoulder pain.Material and methodsOne hundred and six patients (mean age: 43 ±12 years) undergoing gynaecologic laparoscopic surgery (LS) were included. The patients were divided into three groups: group 1 consisted of patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Incidence of wound pain differed at two occasions, 4 and 24 h after surgery, in favor of the control group. [25,26]. Two studies by Tsai et al and one study by Güngördük did not find any difference between groups regarding neither incidence nor intensity of wound pain [6,7,27].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Incidence of wound pain differed at two occasions, 4 and 24 h after surgery, in favor of the control group. [25,26]. Two studies by Tsai et al and one study by Güngördük did not find any difference between groups regarding neither incidence nor intensity of wound pain [6,7,27].…”
Section: Discussionmentioning
confidence: 91%
“…Duration of surgery in the PRM group was a few minutes longer than in the control group. 10 of 11 prior studies indicate that PRM do not prolong surgery [ 3 , 4 , 6 , 7 , 9 , 13 , 14 , 25 – 27 ]. A reason surgical duration was slightly longer in our PRM group could be that the operating team had varying experience of the maneuvre.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies compared control group (passive abdominal pression) with PRM alone. [16][17][25][26][27][28][29][30][31][32][33][34][35][36] Three studies compared abdominal pression with PRM combined with intraperitoneal saline instillation. [33,[35][36]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The pulmonary recruitment maneuver (PRM) has emerged as an effective way of reducing PLSP through increasing the intraperitoneal pressure and assisting the evacuation of the remaining carbon dioxide. In a recent trial from our institute, it was shown that the PRM with 30 to 40 cm H 2 O pressure in a semi-Fowler position (30° head-of-bed elevation) leads to a significant reduction in PLSP compared to the PRM in the neutral position or compared to the passive evacuation of the abdominal carbon dioxide without the PRM [ 2 ]. However, the PRM with higher pressure carries the risk of pulmonary barotrauma complications and hemodynamic deterioration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%